Performance curve approach to optimising fluidising water for Knelson concentrators - Subasinghe, Nimal (Maney Publishing, 2012)
Centrifugal concentrators such as Knelson concentrators (KCs) are commonly used in most goldprocessing plants to recover fine liberated gold particles. The decision to employ a gravityrecovery circuit is primarily based on the amount of gravity recoverable gold (GRG) in the oreamong other considerations. However, the conditions required to optimise the gold recovery insuch devices used in plants cannot be determined by GRG test results as the separation ofparticles is based on the particle bed dynamics within the given unit which are different to thoseencountered in a three inch KC used for the GRG test. The significant operating variables thataffect the performance of a KC are the size distributions of the gold and gangue, rotational speedof the bowl, fluidising water flowrate and the cycle time. Of these variables, the rotational speed isgenerally fixed, and the size distributions of the gold and gangue are determined by thecomminution circuit employed. Thus, the fluidising water is the key variable that can be used tocontrol the dilation of the particle bed to maximise the recovery of gold. This paper examines thevalidity of the GRG test for performance evaluation and discusses an alternative method based onperformance curve of the device that can be used to evaluate the optimum fluidising waterflowrate of an operating machine. The principles of determining the performance curve of themachine and its use are also discussed and illustrated with laboratory and plant data.